2008
DOI: 10.1007/s10021-008-9135-2
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Size and Leaf Area Index in Fagus sylvatica Forests: Competing Effects of Precipitation, Temperature, and Nitrogen Availability

Abstract: Plants across diverse biomes tend to produce smaller leaves and a reduced total leaf area when exposed to drought. For mature trees of a single species, however, the leaf area-water supply relationship is not well understood. We tested the paradigm of leaf area reduction upon drought by a transect study with 14 mature Fagus sylvatica forests along a steep precipitation gradient (970-520 mm y )1 ) by applying two independent methods of leaf size determination. Contrary to expectation, average leaf size in dry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
85
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 68 publications
(33 reference statements)
22
85
2
1
Order By: Relevance
“…For example, leaf and total litter values for the unthinned plot were higher than those reported for various beech forests aged 47-200 years (Matteucci et al 1999), and for beech forests aged 83-147 years in France (Lebret et al 2001). In addition, leaf area index values were higher than those observed in other Italian beech forests (Cutini 2002), and agreed with those from other studies (Lebourgeois et al 2005;Meier and Leuschner 2008). This outcome is important because medium-high stand productivity (with reference to canopy attributes) represents one of the main requirements for improving forest management systems, particularly regarding the conversion of coppice woods.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For example, leaf and total litter values for the unthinned plot were higher than those reported for various beech forests aged 47-200 years (Matteucci et al 1999), and for beech forests aged 83-147 years in France (Lebret et al 2001). In addition, leaf area index values were higher than those observed in other Italian beech forests (Cutini 2002), and agreed with those from other studies (Lebourgeois et al 2005;Meier and Leuschner 2008). This outcome is important because medium-high stand productivity (with reference to canopy attributes) represents one of the main requirements for improving forest management systems, particularly regarding the conversion of coppice woods.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, the use of ecological variables in our analyses allowed an objective and broadly comparable evaluation of the influence of the applied management options. The selected variables and experimental designs used were in accordance with that of other studies specifically addressing beech forest dynamics (e.g., Chianucci and Cutini 2013;Genet et al 2010;Lebourgeois et al 2005;Leuschner et al 2006;Meier and Leuschner 2008). Based on comparisons with these reports, we conclude that our studied stands are characterized by medium-high productivity, as revealed by the average values of canopy attributes.…”
Section: Resultssupporting
confidence: 70%
“…Buds of oak and beech were formed in late summer, in line with previous studies (55,56). Leaf flushing observations were conducted on the terminal bud of each individual sapling, according to the following phenology scale: (1) undeveloped bud: bud still in winter dormancy; (2) swollen bud: green or elongated bud with broken scales; (3) leaf flushing: leaf bases still hidden in bud scales but leaf tips detached from the bud axis; and (4) leaf unfolded: the entire leaf blade and the leaf stalk were visible.…”
Section: Methodssupporting
confidence: 91%
“…Similar results were also obtained by Meier and Leuschner (2008) for Fagus sylvatica stands in central Germany. Authors concluded that stand leaf area of the beech along this precipitation gradient is not a simple function of water availability, but is controlled by several abiotic factors including spring temperature and possibly also nitrogen supply, which both tend to increase toward drier sites, thus overlaying any negative effect of water shortage on leaf development.…”
Section: Raspravasupporting
confidence: 87%